MEXICAN EXPERIENCES OF B. TRAVEN: THE POSSIBILITY OF IMAGOLOGICAL READING - MANDRYKO, Olga (Accents and Paradoxes of Modern Philology, 2022)
The article presents the historical-literary analysis of The Cotton-Pickers (Die Baumwollpflücker), the first novel by the German writer B. Traven, who spent most of his intellectual life living and writing (in German) in Mexico, where he died, and focused his main works on the life of the native people of the state of Chiapas. The Cotton-Pickers did not emphasize the issue of the native population, whose representatives only appear episodically in the text, and described the experience of the author-narrator who recently arrived in Mexico in his search for work. Until today, this novel has been analyzed mainly as an autobiographical text and from a sociological perspective, highlighting the author’s leftist attitude. However, it has not been taken into account how B. Traven is creating, throughout the narrative, a cultural image of the country that enchanted him throughout his life. The social and cultural aspects of the Mexican Revolution, those that attracted the author who, at the same time, does not stop being critical about the current state of things, are highlighted too. In this way, an imagological perspective is proposed in the reception of the work. Likewise, despite the fact that B. Traven’s researchers always underlined his leftist orientation (anarchist in nature) in the reception of this revolution, few were those who valued the emphasis he placed on the role of the native population in the revolutionary process. Meanwhile, B. Traven described the role and destiny of the Indians in the revolution earlier than Mexican-born writers did it. It was he who wrote the first novels in Mexico that presented the Indians as active participants in the revolutionary processes. And it was also he who placed special emphasis on the autochthonous component as the spiritual core of the Mexican nation and on its role in the hopeful future of the country.